An Examination of Loading Profiles for Youth Athletes Performing the Hang Power Clean - Kelton Mehls; Sarah Martinez; Connor Edwards (International Universities Strength and Conditioning Association, 2021)
This study aimed to examine the loading profiles of youth athletes during the hang power clean to determine optimal loading parameters for force, power, rate of force development, and barbell velocity. Sixteen male youth athletes performed three repetitions of the hang power clean at 10% intervals ranging from 30-90% of their one-repetition maximum (1RM). One-way repeated measures ANONAs revealed that training load had a significant effect on the peak and average of all variables examined (p < 0.05). Most notably, peak power was maximized at 70% 1RM which was not significantly different 60-90% 1RM. Peak rate of force development was maximized at 90% 1RM, though it was not significantly greater than 50-90%1RM. Conversely peak barbell velocity was maximized at 30% 1RM which was significantly greater than 50-90% 1RM. While the results for power are similar to that of older, stronger athletes, the youth population in this study maximized barbell velocity and rate of force development at different training loads compared to more developed athletes. These results seem to suggest that youth athletes need to achieve a higher level of strength before they are capable of training with high relative training loads while maintaining high barbell velocities.